Analisis Kesantunan Berbahasa dalam Teks Pidato Gubernur Aceh dan Pelaksana Tugas Gubernur Aceh Tahun 2018—2019 - Ningsih, Ria Mardi; Armia, Armia; Idham, Muhammad (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
This research is entitled "Analysis of Language Politeness in the Text of the Speech of the Governor of Aceh and Acting of the Governor of Aceh in 2018-2019". The formulation of the problem is (a) what is the politeness of the language in the speech text of the Governor of Aceh and plt. Governor of Aceh in 2018-2019, (b) what maxims appear in the speech text of the Governor of Aceh and plt. The Governor of Aceh in 2018-2019, and (c) what kind of maxims were used most dominantly by the Governor of Aceh and plt. Governor of Aceh. The purpose of this research is to describe (a) the politeness of language in the speech text of the Governor of Aceh and plt. Governor of Aceh, (b) what maxims appear in the text of the speech of the Governor of Aceh and plt. The Governor of Aceh, and (c) what maxims appear most in the text of the speeches of the Governor of Aceh and plt. Governor of Aceh. This study uses a qualitative approach with descriptive methods. The data of this study were sourced from utterances contained in the speech text of the Governor of Aceh and plt. Governor of Aceh 2018-2019. The data collection technique was carried out using document review techniques. The data were analyzed through four stages, namely; (a) identification, (b) classification, (c) analysis, and (d) description. The result of this study can be stated as follows. First, the language contained in the text of the speech of the Governor of Aceh and plt. The governor of Aceh is a polite language. Second, the maxims contained in the text of the Governor of Aceh and plt. The Governor of Aceh, namely the maxim of wisdom, the maxim of generosity, the maxim of humility, the maxim of approval, the maxim of acceptance, and the maxim of sympathy. Third, the maxim of wisdom is the maxim that appears most frequently in the speech texts of the Governor of Aceh and plt. Governor of Aceh.